2008
DOI: 10.3171/foc.2008.25.11.e3
|View full text |Cite
|
Sign up to set email alerts
|

Activated autologous macrophage implantation in a large-animal model of spinal cord injury

Abstract: Object Axonal regeneration may be hindered following spinal cord injury (SCI) by a limited immune response and insufficient macrophage recruitment. This limitation has been partially surmounted in small-mammal models of SCI by implanting activated autologous macrophages (AAMs). The authors sought to replicate these results in a canine model of partial SCI. Methods Six dogs underwent left T-13 spinal cord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…First, following the idea that inflammatory cells might help to clear debris inhibitory to axonal growth, 99,100 autologous transplants of activated macrophages were tested in a T13-L1 hemisection model. 101 This study first examined pilot data on 7 dogs (including 1 sham dog, 2 culture media-only dogs, and 4 cell transplant dogs) but found no motor or electrophysiologic benefit of the transplant over a 9-month period, and the experiment was terminated. In 4 other studies a positive effect of the transplant, composed of MSCs derived from adipose tissue, bone marrow, Wharton jelly, or umbilical cord blood, was found.…”
Section: Cell Transplantation In Experimental Canine Models Of Spinalmentioning
confidence: 99%
“…First, following the idea that inflammatory cells might help to clear debris inhibitory to axonal growth, 99,100 autologous transplants of activated macrophages were tested in a T13-L1 hemisection model. 101 This study first examined pilot data on 7 dogs (including 1 sham dog, 2 culture media-only dogs, and 4 cell transplant dogs) but found no motor or electrophysiologic benefit of the transplant over a 9-month period, and the experiment was terminated. In 4 other studies a positive effect of the transplant, composed of MSCs derived from adipose tissue, bone marrow, Wharton jelly, or umbilical cord blood, was found.…”
Section: Cell Transplantation In Experimental Canine Models Of Spinalmentioning
confidence: 99%
“…However, a second surgery might also eliminate nerve fibers that had been spared initially and cause sufficient trauma to reduce the effects of local circuit activity. A single attempt to replicate this approach in a dog model failed to demonstrate axon growth-promoting effects of autologous macrophage transplantation [57]. In a phase I clinical trial begun in 2000, surgical implantation of autologous macrophages was found to be feasible in acute SCI patients and without adverse effects [58].…”
mentioning
confidence: 98%
“…The resulting increase in functional recovery relative to untreated animals was suggested to be related to the bridging of the defect by nerve fibres. While the data of that study and others provided the basis for a Phase I clinical trial (Knoller et al, 2005), a subsequent animal study in dogs failed to demonstrate a benefit of implanting macrophages into a spinal cord injury (Assina et al, 2008). Clearly, macrophages play a role of considerable complexity that is continuing to be elucidated.…”
Section: Discussionmentioning
confidence: 99%